Electrooxidation‐Induced C(sp3)–H/C(sp2)–H Radical‐Radical Cross‐Coupling between Xanthanes and Electron‐Rich Arenes. Issue 12 (6th April 2022) - Liang, Yuwei; Niu, Linbin; Liang, Xing‐An; Wang, Shengchun; Wang, Pengjie; Lei, Aiwen
Comprehensive Summary: The arylation of C(sp 3 ) − H bonds has been a priority research topic in organic synthesis. Minsici reactions have been the powerful methods for C(sp 3 ) − C(sp 2 ) bonds formation. Despite its mature development, the scopes of arenes are usually suitable for electron‐deficient heterocyclic compounds, rather than electron‐rich arenes. Herein, we report an electrooxidation‐induced alkylation of electron‐rich arenes with H2 evolution under exogenous oxidant‐free conditions, avoiding the utilization of metal catalysts. This protocol is well performed with various electron‐rich aniline derivatives and nitrogen‐containing heterocyclic compounds. We anticipate that this electro‐oxidative C(sp 3 ) − H arylation represents an important expansion for the classic arenes alkylation, thereby proving an attractive strategy for the developments of radical cross‐coupling chemistry. Abstract : The arylation of C(sp 3 )–H bond has always been a priority research topic in organic synthesis. Despite their mature development, most of them are only suitable for electron‐deficient heterocyclic compounds, limiting further application. Herein, we report an electrooxidation‐induced alkylation of electron‐rich arenes with H2 evolution under metal‐ and oxidant‐free conditions. This method is well performed with various electron‐rich arenes, including different aniline derivatives and nitrogen containing heterocyclic compounds.